Community-based organizations role on coastal resource management in the Sarangani Bay Area - Calva, Joy C. (2018)
In areas along Sarangani Bay, there is a substantial supply of marine resources. Unfortunately, the demands, at times, exceed the supply, so intervention like establishing Coastal Resource Management (CRM) is an important mechanism to sustain resources. This study documented the community-based initiatives of various organizations among municipalities and barangays along Sarangani Bay that support its role in the coastal resource management in the area. Also identified are the factors affecting the aforementioned role. The researcher employed Key Informant Interview (KII) among officers and members of organizations and officials of local government units (LGU) in the municipalities of Sarangani Province and General Santos City (SARGEN) and also retrieved available documents for content analysis. It is evident that crucial to the success of the community-based organizations is the support and funding coming from local and international agencies in order to initiate putting of marine protected areas, implementing bantam-dagat, promoting clean-up drive and solid waste management, and introducing alternative livelihood projects. There are two success stories that serve as proofs of continuing initiatives of the organizations, Further, there are factors that either facilitate or hinder the success of the community-based organizations.
Keywords: Coastal resource managemet; Sarangani Bay; Mindanao studies